2010
DOI: 10.1007/s10549-010-0868-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breast cancer screening behavior in women with a strong family history of the disease

Abstract: This study applied the self-regulation model to examine cognitive and emotional predictors of screening in unaffected women with a strong family history of breast cancer. 748 unaffected female members of an Australian registry of multiple-case breast cancer families formed the sample. Participants completed a baseline psychosocial questionnaire and a screening questionnaire 3 years later. Multinomial logistic regression was employed to determine predictors of under- and over-screening according to national gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 30 publications
7
44
2
1
Order By: Relevance
“…Consistent with this finding, other studies also reported that women with a history of breast cancer in the family have more information on breast cancer, susceptibility and awareness of screening tests than other women (Dündar et al, 2006;Tastan et al, 2011). More specifically, Price et al (2010) found that the rate of the women with a history of breast cancer in the family who have had the experience of mammography is 74%. Therefore, these findings suggest that these women have higher levels of information about both breast cancer and related risk factors, and that they much more frequently employ the screening methods.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this finding, other studies also reported that women with a history of breast cancer in the family have more information on breast cancer, susceptibility and awareness of screening tests than other women (Dündar et al, 2006;Tastan et al, 2011). More specifically, Price et al (2010) found that the rate of the women with a history of breast cancer in the family who have had the experience of mammography is 74%. Therefore, these findings suggest that these women have higher levels of information about both breast cancer and related risk factors, and that they much more frequently employ the screening methods.…”
Section: Discussionsupporting
confidence: 61%
“…Age was significant in the multivariate model, and, holding all other variables constant, it was found that each year of increased age was associated with a 7% greater likelihood of reattendance; in fact, likelihood of reattendance doubled with each decade of age. This agrees with the thrust of the literature that older age is predictive of greater reattendance as well as adherence to such breast-cancer screening practices as mammography ((Pakenham et al, 2000;Price et al, 2010;Rahman et al, 2005). We view this as logical because older patients would have more stability and security in their lives, personified by long-term relationships, having children, and more established career patterns.…”
Section: Discussionsupporting
confidence: 87%
“…Depression reduces adherence to treatment 65,66 and interferes with participation in preventive health care. 67,68 Depression is also associated with important risk factors for physical illness, including sedentary lifestyle, 69 obesity, 70 and cigarette smoking. 71 The pathophysiology of depression appears to be related to other fundamental mechanisms of disease (e.g., MDD shares a complex and bidirectional relationship with obesity and associated metabolic problems 70,72 ) and is associated with immune-inflammatory dysfunctions that are implicated in reduced neural plasticity and neuroprogression.…”
Section: What Is the Impact Of Mdd On Physical Health?mentioning
confidence: 99%